The effect on business performance of marketing strategies implemented against the crises - Akkaşoğlu, Süleyman; Ulema, Şevki (Anais Brasileiros de Estudos Turísticos, 2024)
The aim of the research was to identify the impact of marketing strategies implemented by hotel businesses in response to crises on business performance. Four & five-star hotels in the Antalya and Istanbul provinces constituted the universe of the research. The data were collected by questionnaire. Consequently, it was found that the hotel businesses are affected at a higher degree by the political and economic crises and that the businesses benefit more intensively from marketing strategies aimed at gaining customers and competition against the crises. As a consequence, it was found out that the crises have a positively effect marketing strategies and a negative impact on the business performance, and that the marketing strategies have a positively effect business performance. It is considered that the study will contribute at the point of well-evaluation of the fact of the crisis with regards to the tourism industry and at the point of positive effect of businesses’ correct marketing strategies on their performance. The study focused on exogenous crises affecting hotel businesses. In future studies, the marketing strategies to be implemented by businesses against endogenous crises may be investigated.